Biomechanical testing of a hybrid locking plate fixation of equine sesamoid osteotomies - da Silveira, E. Almeida; Levasseur, A.; Lacourt, M.; Elce, Y.; Petit, Y. (Veterinary and Comparative Orthopaedics and Traumatology, 2014)
To compare the biomechanical properties of a hybrid locking compression plate (LCP) construct with the compression screw technique as a treatment for transverse mid-body proximal sesamoid bone fractures.Ten paired forelimbs from abattoir horses were used. The medial proximal sesamoid bone of each limb was osteotomized transversely and randomly assigned, to either repair with a two-hole 3.5 mm LCP or a 4.5 mm cortical screw placed in lag fashion. Each limb was tested biomechanically by axial loading in single cycle until failure. The point of failure was evaluated from the loaddisplacement curves. Then a gross evaluation and radiographs were performed to identify the mode of failure.The loads to failure of limbs repaired with the hybrid LCP construct (4968 N ± 2167) and the limbs repaired with the screw technique (3009 N ± 1091) were significantly different (p <0.01). The most common mode of failure was through a comminuted fracture of the apical fragment of the proximal sesamoid bone.The LCP technique has potential to achieve a better fracture stability and healing when applied to mid-body fractures of the proximal sesamoid bone. Further testing, particularly fatigue resistance is required to corroborate its potential as a treatment option for mid-body fractures of the proximal sesamoid bone.
Keywords: Mid-body fracture; proximal sesamoid bone; locking compression plate; biomechanics; horses